FORENSIC ACCOUNTING AND CORPORATE CRIME MITIGATION - Enofe, A.O.; Ekpulu, G.A.; Ajala, T. O. (European Scientific Journal, ESJ, 2015)
The broad objective of this paper is to examine forensic accounting and corporate crime mitigation in Nigeria. The study was prompted by the dearth of research work on forensic accounting and corporate crime mitigation. Descriptive statistics and percentage analysis using Statistical package for social sciences (SPSS 17.0) were used to analyse the responses from the various respondents. Findings from the empirical result indicate that forensic accounting could be a valuation tool in strengthening corporate governance which could help to curb the menace of corporate crime in Nigeria. The researcher made useful recommendations among which are; corporate governance mechanisms should encompass forensic accounting in addition to its composition as contained in the Code of Best Practices on Corporate Governance as issued in 2003. In addition to the introduction of forensic accounting, the auditing profession should also not be left out in this all important innovation by embracing forensic audit to actually unveil fraudulent practices in Nigeria Corporation.